A REVIEW ON RECENT ADVANCES IN HYDROGELS AS DRUG DELIVERY SYSTEM - GHANEM, AYA M.; ASHOUR, SONDOS AHMAD; HUSSIEN, RUAA M. (International Journal of Applied Pharmaceutics, 2025)
Hydrogels are hydrophilic three-dimensional polymeric networks which has the capability to absorb water or biological fluids. These polymeric network is formulated through chemical crosslinking or physical crosslinking mechanisms. Several polymers of synthetic and natural origin can be used to form hydrogels. Mechanical properties, swelling and biological properties are about the most significant hydrogels properties that can affect their morphology and structure. Hydrogels are promising biomaterials due to their significant properties as hydrophilicity, biodegradability, biocompatibility and non-toxicity. These characteristics make hydrogels appropriate for medical and pharmaceutical application. This review discusses the types of hydrogels, their properties, mechanism of preparation and applications of hydrogels as drug delivery system.